Biosorbents and Biosorption of Uranium Ions a Statistical Review - K, Kadambanathan.; S, Theepapriya.; Fathima, Anis (International Journal of Engineering and Technology, 2018)
This study addresses the availability of various biosorbents and significance of characterization techniques used for biosorption of uranium ions. The improvements in nuclear technology have leads to increasing nuclear waste containing uranium being released and exposed in the surroundings.The objective of this paper is to develop a better understanding the various techniques for the water system and environment were polluted with radionuclides (particularly uranium), considering the health effects of uranium, including varieties of biomasses and data of uranium uptake quantity at respective conditions, research issues concerning the biosorption process discussed. The accessibility of equilibrium models or adsorption isotherm is considering for fit the value for biosorption process. Moreover, it gives outlook of adherence and affinity of biomass towards the uranium ions particularly U(VI) was studied. This collective information in uranium adsorption biomasses at different pH and temperature used for U ions uptake. This paper shows the availability of organic living species and howfar it eliminates the toxic ions.Â Â